Role of Plant Volatiles in Atmospheric Processes under Current and Future Climates - Ülo Niinemets (Proceedings, 2023)
Several plant species emit different volatile organic compounds constitutively under typical physiological conditions, and all plant species can be elicited to emit volatiles under stress conditions when physiological activity is curbed. Plant emissions constitute the biggest global source of reactive volatile organic compounds in the atmosphere. These volatiles play major biological roles in plant–plant interactions and in plant interactions with other organisms. In addition, plant-emitted volatiles often dominate the volatile-driven large-scale biosphere–atmosphere processes. In particular, plant volatiles participate in ozone- and secondary organic aerosol (SOA)-forming reactions and in cloud formation. Both enhanced SOA and cloud formation contribute to the cooling of the Earth’s surface, implying that plants can alter their own life environment. At the global scale, amelioration of vegetation growing conditions via volatile emissions can reduce the rate of global environmental change, but there are currently major uncertainties in understanding how plant emissions change in future climates and the quantitative impact of plant emissions on future climate change. Climate change is a complex phenomenon that entails alterations in a series of environmental factors. For plants, climate change is expected to enhance the severity and duration of stress periods when plant physiological activity is strongly reduced. This includes both the enhancement of abiotic stresses such as rising temperatures and more severe drought episodes in many parts of the globe and more devastating biotic stresses such as frequent outbreaks of herbivore and pathogen attacks. These changes in the frequency and duration of stress episodes can strongly impact volatile emissions. Stress typically reduces the emissions of constitutively released plant volatiles and elicits emissions of specific volatiles in a stress-severity-dependent manner. Thus, the plant-dependent feedback on global change is expected to become stronger in more stress-prone climates.